In, but not of, Africa: a divided South Africa faces COVID-19. Issue 1 (2nd January 2021) - Friedman, Steven
ABSTRACT: A feature of the COVID-19 pandemic has been that many 'First World' countries have been less able to prevent illnesses and deaths than some in the 'Third World'. But what if a country is both 'First' and 'Third' World? This article argues that South Africa is such a country and that its response to COVID-19 has been shaped by this reality. That explains why the African country with the most sophisticated health facilities on the continent has experienced almost as many cases and fatalities as the rest of Africa combined.